2004
DOI: 10.1093/geronb/59.1.p19
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Health Problems on Depression and Activities in Middle-Aged and Older Adults: Age and Social Interactions as Moderators

Abstract: In this study, we compared the impact of health problems (HPs) on everyday activities and depressive symptoms between middle-aged and older adults. We also examined what type and source of social interactions moderate the noxious effects of HPs. Longitudinal analyses of data with 1,802 Japanese community-dwelling adults indicated that HPs were significantly related to (a) an increase in depressive symptoms among middle-aged adults and (b) a decline in everyday activities among older adults. The former was buff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
2
14
1
Order By: Relevance
“…This finding coincides with other prevalence studies carried out in recent years, where the increase of these symptoms based on age was identified 6,21,22 . The World Health Organization (WHO) 23 , states that the greatest occurrence of Depression occurs in adults over 65 years old, and highlights the complexity of performing a correct differential diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…This finding coincides with other prevalence studies carried out in recent years, where the increase of these symptoms based on age was identified 6,21,22 . The World Health Organization (WHO) 23 , states that the greatest occurrence of Depression occurs in adults over 65 years old, and highlights the complexity of performing a correct differential diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…Black et al used the words stress, nerves, and depression interchangeably when discussing effects of chronic illness (Fukukawa, Nakashima, Tsuboi, & Nino, 2004). African-American elders have shown that they attribute depression to ''experiencing difficulties'' rather than an illness that requires treatment (Lincoln, Chatters, & Taylor, 2005).…”
Section: Expressions Of Depressionmentioning
confidence: 99%
“…The prevalence of depression is reported to be 15% in women and 10% in men [8]. Moreover, this disorder is related to one's livelihood [9]; thus it is estimated that by 2030 depression would be the most important reason for labor loss [4,10]. Depression is the most common and widespread psychological disorder and occurs in almost every society [4]; however, in underdeveloped and developing countries, it is difficult to determine the prevalence due to the lack of adapted scales and unestablished reliability and validity [11].…”
Section: Introductionmentioning
confidence: 99%